PERANCANGAN SISTEM INFORMASI AKADEMIK MOBILE DENGAN SCRUM FRAMEWORK - Binastya Anggara Sekti; Mohammad Norman Gaza Laksono; Zhafira Anindya Tiaraputri; Mohamad Iqbal Ajie Laksono; Putri Jelita Syifa Eraydya (Universitas Muhammadiyah Gresik, 2023)
A mobile application-based academic information system is an information system that provides academic information for students and lecturers that can be accessed from mobile devices from anywhere. With the existence of a mobile application-based academic information system, students and lecturers can be given alternatives to carry out academic activities on an online academic information system from mobile devices so as to provide convenience and flexibility. The research method was carried out by conducting interviews with lecturers and several students to obtain information about the needs of the academic information system. Meanwhile, the system designer's method uses the Scrum. Scrum is a framework that is suitable to be implemented in making academic information systems because Scrum is used in a work context that is quite complicated where cases cannot be predicted. The result of the implementation is that some of the information in the academic information system that can be accessed is the siakad login page, the siakad dashboard, and others so that it can maximize academic activities which of course can also make it easier for students and lecturers to get services and information about academic matters.